Students’Perception And Practices of Using Tiktok for Learning Speaking Skills in Efl University Contexts - Zumrotul Aulia; Fera Zasrianita; Andriadi Andriadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aimed to investigate students’ perceptions, independent practice strategies, and speaking performance through the utilization of TikTok in an EFL context. This research employed a mixed-methods design involving 38 secondary school students as the primary participants. Data were gathered through a comprehensive collection process utilizing student questionnaires, speaking proficiency tests (short monologue activities), and individual semi-structured interviews. The quantitative results from the questionnaire revealed that the utilization of TikTok was highly valued by the students, where the perceived benefits in enriching vocabulary and pronunciation achieved the highest score at 78%, followed by its convenience for independent practice (72%) and high learning engagement (73%). Furthermore, the students' actual speaking performance in the short monologue activity was categorized as